The Wanganui/Whanganui Debate: A Linguist's View of Correctness - Bauer, Winnifred (Victoria University of Wellington Law Review, 2011)
A decision was taken in 2009 by the Minister of Land Information that the official spelling of the city formerly spelled Wanganui should henceforth be Whanganui, although a period of grace was given for the change-over. Nonetheless, there is still a good deal of opposition to the change from residents, particularly expressed on many occasions by the outspoken mayor at the time, Michael Laws. This article was originally delivered as a seminar during Māori Language Week 2009, before the decision was taken. It seeks to explore the complex issues that underlie such a decision, and thus to shed light on why the issue is still so controversial. With the success of the case against Wanganui, it is clear that this will not be the last instance where a Māori community seeks legal overthrow of the spelling of a name: already the case of Rimutaka versus Remutaka is being debated.